+0  
 
0
117
2
avatar

Find the distances from (-2,-4) to each of (-6, 8), (5,2) and (9, 5).

Guest May 19, 2017
Sort: 

2+0 Answers

 #1
avatar
0

First, know the distance formula:

 

\(d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\)

 

Now, simply substitute the values into this formula and simplify:

 

\(d=\sqrt{(-6-(-2))^2+(8-(-4))^2}\)

\(=\sqrt{(-6+2)^2+(8+4)^2}\)

\(=\sqrt{(-4)^2+12^2}\)

\(=\sqrt{16+144}\)

\(=\sqrt{160}\)

 

Of course, put all radicals in simplest radical form. I also included an approximate decimal to the ten thousandths place:

 

\(\sqrt{160}=\sqrt{16*10}=\sqrt{16}\sqrt{10}=4\sqrt{10}\approx12.6491\)

 

Let's continue this process for the rest of the points. I'll do the distance from (-2,-4) to (-6,8):

 

\(d=\sqrt{(-5-(-2))^2+(2-(-4))^2}\)

\(=\sqrt{(5+2)^2+(2+4)^2}\)

\(=\sqrt{7^2+6^2}\)

\(=\sqrt{49+36}\)

\(=\sqrt{85}\approx9.220\)

 

The square root of 85 is already in simplest radical form, so no need to do anymore.

 

 


 

Guest May 19, 2017
 #2
avatar
0

The previous didn't find the final distance from (-2,-4) to (9,5), so I will:

 

\(d=\sqrt{(9-(-2))^2+(-5-(-4))^2}\)

\(=\sqrt{(9+2)^2+(-5+4)^2}\)

\(=\sqrt{11^2+(-1)^2}\)

\(=\sqrt{121+1}\)

\(=\sqrt{122}\approx11.0454\)

 

The square root of 122 has no perfect square factors, so it is already in simplest radical form.

Guest May 19, 2017

2 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details